DIGITALISASI ADMINISTRASI PENDIDIKAN: TANTANGAN DAN STRATEGI IMPLEMENTASI DI SEKOLAH ISLAM - Dea Khalika Siregar (STKIP Pesisir Selatan, 2026)
This study aims to analyze the implementation of educational administration digitalization in Islamic schools, focusing on identifying challenges, implementation strategies, and the readiness of human resources and supporting infrastructure. This research employs a qualitative approach using a library research method by analyzing various relevant scientific sources, including journal articles, books, and research reports. The findings indicate that digitalization of educational administration plays a strategic role in improving efficiency, accuracy, transparency, and accountability in managing educational institutions. Digital-based systems enable integrated data management and support data-driven decision making. However, the implementation of digitalization in Islamic schools still faces various complex challenges, including limited digital competence among educators, inadequate technological infrastructure, increased administrative workload for teachers, and organizational cultural resistance to change. Furthermore, there are challenges in integrating digital technology with Islamic values that serve as the foundation of education. The study also reveals that the success of digitalization is strongly influenced by appropriate implementation strategies, such as organizational readiness assessment, human resource capacity building, transparent communication, user-friendly technology selection, and continuous monitoring and evaluation.